Balancing Innovation and Limitations: A Review of Language Learning Technologies - Bastian, Arif Alexander (PROJECT (Professional Journal of English Education), 2025)
This study explores the advantages and disadvantages of using technology in language learning, focusing on tools such as Computer-Assisted Language Learning (CALL), mobile applications, and online learning platforms. Through a review of recent literature, it is evident that technological tools significantly enhance language acquisition, particularly in listening, reading, vocabulary development, and pronunciation. CALL systems, with their multimedia and interactive features, have been shown to improve learner engagement and retention, while mobile applications offer flexibility and autonomy, allowing learners to study at their own pace. However, challenges remain, including the lack of teacher-student interaction in online platforms, reduced opportunities for real-time communication, and potential issues with learner motivation and consistency. The findings suggest that a blended learning model, combining the strengths of technology with the guidance of traditional classroom instruction, provides the most effective approach to language learning. Teachers play a crucial role in structuring learning experiences, offering feedback, and maintaining learner engagement. While technology has the potential to transform language education, its integration requires careful planning to address its limitations. Further research is needed to evaluate the long-term impacts of digital tools and to refine strategies for their effective use.